The joint mechanical function and control of the front leg during cricket fast bowling: a 3D motion analysis study - Ferdinands, R. E. D.; Sinclair, P. J.; Stuelcken, M. C.; Greene, A. J. (Sensors, 2026)
What are the main findings?